2001
DOI: 10.1063/1.1351539
|View full text |Cite
|
Sign up to set email alerts
|

Interdiffusion of CdS and Zn2SnO4 layers and its application in CdS/CdTe polycrystalline thin-film solar cells

Abstract: Toward a high Cu2ZnSnS4 solar cell efficiency processed by spray pyrolysis method J. Renewable Sustainable Energy 5, 053137 (2013); 10.1063/1.4825253 Dependence of efficiency of thin-film CdS/CdTe solar cell on optical and recombination losses J. Appl. Phys. 113, 093105 (2013); 10.1063/1.4794201 Impedance spectroscopy of thin-film CdTe/CdS solar cells under varied illuminationIn this work, we found that the interdiffusion of the CdS and Zn 2 SnO 4 ͑ZTO͒ layers can occur either at high temperature (550-650°C) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
41
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(42 citation statements)
references
References 4 publications
0
41
0
1
Order By: Relevance
“…Up to now, most researches have focused on the synthesis and application of Zn 2 SnO 4 films and nanoparticles. For example, integration of Zn 2 SnO 4 thin film in CdS/CdTe solar cell as buffer resulted in improved device performance [13]. Zn 2 SnO 4 nanoparticles have been used as photocatalysts for degradating organic pollutant [14,15] and as anode in Li-ion batteries [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, most researches have focused on the synthesis and application of Zn 2 SnO 4 films and nanoparticles. For example, integration of Zn 2 SnO 4 thin film in CdS/CdTe solar cell as buffer resulted in improved device performance [13]. Zn 2 SnO 4 nanoparticles have been used as photocatalysts for degradating organic pollutant [14,15] and as anode in Li-ion batteries [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, reducing the CdS thickness can adversely impact device open-circuit voltage (V oc ) and fill factor (FF). We have previously reported that by integrating a high-resistivity zinc stannate (ZTO) buffer layer between the poly-CdS and poly-CdTe films, we can minimize these detrimental effects [4]. Third, there is a nearly 10% lattice mismatch between the poly-CdTe film and the poly-CdS film, which causes the high defect density at the junction region.…”
mentioning
confidence: 98%
“…The most popular TCO, tin-doped indium oxide (ITO) has some shortcomings limiting its applications in PVs and OLED structures [2,3]. This stimulated an intense research on alternative TCO materials and is now the subject of numerous investigations for alternative material to ITO for PVs device structures [4]. From the literatures, Cd 2 SnO 4 thin films are an n-type defect semiconductor material exhibiting promising properties such as low metallike electrical resistivity (10 -6 :m) and high transmission (>90%) in the visible range of the light spectrum and high reflectivity in the IR range.…”
Section: Introductionmentioning
confidence: 99%